Identification of pathogens causing fever in returning travelers using next-generation sequencing - Kenji Gotoh; Nobuyuki Hamada; Takahito Kashiwagi; Koyu Hara; Hiroshi Watanabe (Tropical Medicine and Health)
Abstract Introduction In cases of fever following international travel, medical evaluation should consider the prevalence of infectious diseases in the travel destination. However, there are instances where a definitive diagnosis cannot be made. Identifying these unknown pathogens is crucial for managing febrile returning travelers and as a model for the early detection of emerging infectious diseases. The aim of this study was identification of pathogens from febrile cases where fever was the primary symptom and no other specific clinical features were present. Methods Between 2008 and 2020, a total of 164 travelers visited Kurume University Hospital due to illness after returning from abroad. However, despite extensive testing, no definitive diagnosis was reached for 18 febrile travelers. Next-generation sequencing (NGS) was performed on eight samples (five whole blood, one serum, one cerebrospinal fluid, and one nasopharyngeal swab) collected from seven returning travelers with undiagnosed fever. Additionally, virus isolation using VeroE6 cells was conducted on two of these samples. Results NGS detected human coronavirus OC43 (HCoV-OC43) genes in all eight samples. Of these, six samples contained only HCoV-OC43 genes, one sample contained both HCoV-OC43 and herpes simplex virus type 1 (HSV-1) genes, and one sample contained both HCoV-OC43 and mumps virus genes. Furthermore, conventional RT-PCR confirmed the presence of HCoV-OC43 genetic fragments in two of the eight samples. Conclusion Our findings suggest that before the COVID-19 pandemic, common coronaviruses such as HCoV-OC43 were a frequent cause of fever in returning travelers. If tropical infectious diseases, such as dengue fever and malaria, are excluded and the patient’s general condition remains stable, outpatient follow-up is a viable option.